What Do We Do about Helicobacter pylori?. (1st May 1999) - Hawkey, CJ
Abstract : Heliobacter pylori and nonsteroidal anti-inflammatory drugs (NSAIDs) cause ulcers by different mechanisms. Under some circumstances, patients infected with H pylori may be less prone to NSAID-associated ulcers than those who are H pylori -negative. Eradication trials have yielded differing results. However, those who have studied patients who have a past history of ulcer disease and are already established on NSAIDs have shown no benefit from H pylori eradication.